2018
DOI: 10.2136/sssaj2017.04.0120
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil Physical Properties and Carbon Protection Mechanisms by Surface Application of Lime in a Tropical No‐Tillage System

Abstract: Liming helped avoid structural degradation. Liming effectively increased the stabilization of soil organic matter. More stable soil structure was achieved by liming. Long‐term no‐till soils often have layers that are severely affected by physical and chemical degradation. Soil acidity is associated with physical problems, such as higher bulk density, that restrict root growth and crop production, especially in tropical regions with dry seasons. Liming is the most common practice adopted to alleviate soil acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Both initial sieving conditions resulted in greater C concentration of macroaggregates compared with microaggregates ( p < 0.001). Greater soil organic C concentration in water‐stable macroaggregates than in water‐stable microaggregates is consistent with investigations in some tropical studies (Carmeis Filho et al., 2018; Sarker et al., 2018), but not in others (Madari et al., 2005). In this latter study with 19 mm initial screen size, macroaggregate C concentration was lower than microaggregate C concentration under native forest, but similar between aggregate fractions under conventional‐till and no‐till cropland.…”
Section: Resultssupporting
confidence: 90%
“…Both initial sieving conditions resulted in greater C concentration of macroaggregates compared with microaggregates ( p < 0.001). Greater soil organic C concentration in water‐stable macroaggregates than in water‐stable microaggregates is consistent with investigations in some tropical studies (Carmeis Filho et al., 2018; Sarker et al., 2018), but not in others (Madari et al., 2005). In this latter study with 19 mm initial screen size, macroaggregate C concentration was lower than microaggregate C concentration under native forest, but similar between aggregate fractions under conventional‐till and no‐till cropland.…”
Section: Resultssupporting
confidence: 90%
“…Even though the experience of Coventry et al () and Carmeis et al () suggested that liming could increase enhancing infiltration when the soil is ripped, Table indicates that the 2014 seasonal runoff for the limed plots of Transect‐1 ranked highest of the three transects. The opposite was true in the previous 2 years where the plot with conventional tillage and no liming in Transect‐1 ranked lowest in runoff among transects (Figure S1).…”
Section: Resultsmentioning
confidence: 91%
“…Even though the experience of Coventry et al (1987) and Carmeis et al (2018) suggested that liming could increase enhancing infiltration when the soil is ripped, Table 2 indicates that the 2014 seasonal runoff for the limed plots of Transect-1 ranked highest of the three transects. The opposite was true in the previous 2 years where the plot with conventional tillage and F I G U R E 3 Mean monthly rainfall distribution for 5 years average (1989)(1990)(1991)(1992)(1993) and monthly rainfall distribution of year 2012, 2013, and 2014 in Anjeni watershed during the crop growing period [Colour figure can be viewed at wileyonlinelibrary.com] no liming in Transect-1 ranked lowest in runoff among transects (Figure S1).…”
Section: Effect Of Depth Of Ripping and Liming On Runoff Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface liming under a no-till system improves soil aggregation by increasing the average aggregate diameter in the layer (0-0.01 m), but without the same effect on the layer (0.02-0.1 m) (Ferreira et al, 2019). Carmeis et al, (2018) the superficial liming in the no-till system increased the amount of soil macroaggregates at a depth of 0-0.4 m, but the effect magnitude varied according to the applied limestone dose and soil depth. Further, the increase in average aggregate diameter shows a positive correlation according to the increase in applied limestone doses.…”
Section: 21effects Of Liming On Soil Aggregatesmentioning
confidence: 92%